2006
DOI: 10.1038/ng1940
|View full text |Cite
|
Sign up to set email alerts
|

HAX1 deficiency causes autosomal recessive severe congenital neutropenia (Kostmann disease)

Abstract: Autosomal recessive severe congenital neutropenia (SCN) constitutes a primary immunodeficiency syndrome associated with increased apoptosis in myeloid cells, yet the underlying genetic defect remains unknown. Using a positional cloning approach and candidate gene evaluation, we identified a recurrent homozygous germline mutation in HAX1 in three pedigrees. After further molecular screening of individuals with SCN, we identified 19 additional affected individuals with homozygous HAX1 mutations, including three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
428
1
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 450 publications
(459 citation statements)
references
References 27 publications
8
428
1
12
Order By: Relevance
“…Performance of bone marrow aspiration and trephine biopsy in deep sedation was strongly encouraged. If marrow morphology shows maturation arrest at the stage of pro-myelocyte/myelocyte AE the presence of a cytogenetic clone, then the diagnosis of severe congenital neutropenia (SCN) is considered as appropriate (EO, 8.6, B) and the study of ELA2 and HAX-1 [12,[50][51][52] mutations, as the most frequently involved genes, were recommended by the panel (EO, 8.6, B). In presence of genital-cardiac malformations the lesion of G6PC3 gene has to be considered [53].…”
Section: (Eo 9 A)mentioning
confidence: 99%
“…Performance of bone marrow aspiration and trephine biopsy in deep sedation was strongly encouraged. If marrow morphology shows maturation arrest at the stage of pro-myelocyte/myelocyte AE the presence of a cytogenetic clone, then the diagnosis of severe congenital neutropenia (SCN) is considered as appropriate (EO, 8.6, B) and the study of ELA2 and HAX-1 [12,[50][51][52] mutations, as the most frequently involved genes, were recommended by the panel (EO, 8.6, B). In presence of genital-cardiac malformations the lesion of G6PC3 gene has to be considered [53].…”
Section: (Eo 9 A)mentioning
confidence: 99%
“…Severe congenital neutropenia is caused by loss-of-function mutations in a variety of proteins including the genes encoding neutrophil elastase, HAX1, and the recently identified glucose-6-phosphatase catalytic subunit 3 (Ancliff, 2003;Klein et al, 2007;Boztug et al, 2009). The XLN-WASP mutations (L270P, S272P, and I294T) add to the genetic complexity of the disease (Devriendt et al, 2001;Ancliff et al, 2006;Beel et al, 2009).…”
Section: Br Ief Definitive Repor Tmentioning
confidence: 99%
“…Recent studies involving knock-out mice for each of these components provided evidence that only Cyp-D represents a necessary regulatory component for the PTP opening mechanism, whereas adenine nucleotide translocase and voltage-dependent anion channel participate in the process to a limited extent (18 -22). Disruption in the mitochondrial membrane potential (MMP) due to the opening of the PTP has profound consequences for mitochondrial respiration, energy production, and hence, cell survival.Recent studies have shown that Hax-1 is essential for maintenance of the MMP in myeloid and epithelial cells (23,24). Hax-1 was originally identified by a yeast two-hybrid screen, associating with HS-1 (hematopoietic lineage cell-specific protein 1), a major…”
mentioning
confidence: 99%